Peranan Locus of Control, Self-Esteem, Self-Efficacy, dan Prestasi Belajar terhadap Kematangan Karir - Safitri; Puji Lestari Prianto; Patricia (Fakultas Psikologi Universitas Pancasila, 2010)
The objective of the study was to find out the most dominant factor, among locus of control, self-esteem, self-efficacy and academic achievement, which contributed to career maturity. This was a non-expreimental field study involving 116 respondents who were students of SMAN 112, a state high school in Jakarta. Measurement tools used in this study were locus of control scale which was modified from Taganing's tool (2006), self-esteem scale adapted from self-esteem inventory created by Coopersmith (1967), self-efficacy scale by Zulkaida et.al and career maturity by Taganing (2006). Result showed that the four factors had equal contribution of 7.1 percent towards career maturity. However, this figure was not significant because the respondents came from a school with distinctive quality. Also, respondents had homogenous characteristics.